Tropical sprue: case report with review of literature - Robinson, W; Bhattacharya, B (Journal of Pathology of Nepal, 2012)
Tropical sprue is an important cause of malabsorption in adults and in children in South Asia. Investigations to exclude specific infective, immunological or inflammatory causes are important before considering tropical sprue as a diagnosis. Malabsorption disorders of the small intestine can be a source of great debilitation to the patient, and a diagnostic challenge to the pathologist. This article presents clinicopathological findings of a non coeliac tropical sprue in a 66–year-old male and discusses the histological and clinical information that can help differentiate coeliac from non coeliac sprue. DOI: http://dx.doi.org/10.3126/jpn.v2i3.6030 JPN 2012; 2(3): 241-244